A high-barrier easy-to-tear composite film and a preparation method thereof
Patent Information
- Application Number
- CN202611219500.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-12
- Publication Date
- 2026-10-13
AI Technical Summary
[0005]公告号为CN109774281B的中国专利申请公告了一种抗菌型高阻隔易撕复合膜及其制备方法,该方案中加入纳米无机盐进而提高基材层本身的阻氧阻水性,但是纳米无机盐化学本质为无机填料,直接物理混合,容易在体系中团聚,引发应力集中点,降低复合膜的整体质量水平
1.本发明通过铁基柱撑技术对膨润土进行插层改性,有效扩大其片层间距与比表面积,再利用硅烷偶联剂对壳聚糖进行双键化接枝改性,赋予壳聚糖化学聚合活性,进一步复合改性膨润土制备出壳聚糖/膨润土复合凝胶材料,最终依托熔融开环反应,构建出界面结合稳定的共价键合型核壳填料,突破传统无机、有机填料在聚酰胺基体中相容性差、易团聚、界面结合力弱的技术瓶颈,提高复合膜的整体质量;
Abstract
Description
Technical Field
[0001] This invention belongs to the field of composite membrane preparation technology, specifically an easy-tear high-barrier composite membrane and its preparation method. Background Technology
[0002] Polyamide films, with their excellent mechanical strength, puncture resistance, flexibility, and temperature resistance, are among the most widely used substrates in high-barrier packaging. The PA6 / MXD6 blend system combines the excellent processing properties of PA6 with the ultra-high gas barrier properties of MXD6, and is widely used in mid-to-high-end packaging applications such as food preservation, vacuum sealing, and pharmaceutical protection. However, existing traditional PA6 / MXD6 blend films generally have significant performance shortcomings: the microstructure of pure resin blends is disordered, resulting in irregular crack propagation when the film tears, easily producing serrated tear surfaces and failing to achieve a straight, easy-to-open tear, thus failing to meet the current demand for convenient packaging. Improving tearability through conventional toughening and modifying agents disrupts the dense resin structure, causing a significant decrease in film barrier performance. This has long presented a technical challenge of mutually restricting and difficult-to-balance performance between tearability and barrier properties.
[0003] To improve the overall performance of polyamide films, existing technologies often use inorganic bentonite, silica, and other powders to fill and modify polyamide films, utilizing the inorganic layered structure to extend the gas permeation path and enhance the film's barrier properties. However, traditional physical blending modification methods rely solely on weak interfacial interactions, resulting in extremely poor compatibility between inorganic powders and the polyamide matrix. This easily leads to problems such as powder agglomeration, interfacial voids, and numerous microscopic defects. Not only does this fail to stably improve film barrier properties, but it also causes a decline in film mechanical properties and a deterioration in surface smoothness. Furthermore, uneven filler dispersion results in poor tear consistency and low yield. In addition, conventional organic modified fillers suffer from poor thermal stability, easy decomposition and release during high-temperature processing, and insufficient weather resistance, making them unsuitable for the industrial processing of polyamides, such as high-temperature melt extrusion and biaxial stretching.
[0004] Meanwhile, existing easy-tear high-barrier films mostly adopt a single-formula blending structure. To achieve the desired tearability, a high proportion of additives or functional fillers are usually required, which can easily lead to problems such as additive migration and precipitation, reduced film composite strength, and deterioration of printability. Furthermore, the overall film brittleness is significantly increased, making it prone to breakage during storage and transportation, resulting in insufficient reliability. Currently, there is a lack of a polyamide composite film preparation technology that can precisely control the microstructure, maintain stable interfacial bonding, balance excellent linear tearability and ultra-high barrier properties, and is suitable for industrial mass production. Therefore, this invention proposes an easy-tear high-barrier composite film and its preparation method to address the many shortcomings of existing technologies.
[0005] Chinese patent application CN109774281B discloses an antibacterial high-barrier easy-tear composite film and its preparation method. In this method, nano-inorganic salts are added to improve the oxygen and water barrier properties of the substrate layer itself. However, nano-inorganic salts are inorganic fillers in nature. Direct physical mixing can easily cause them to agglomerate in the system, causing stress concentration points and reducing the overall quality level of the composite film. Summary of the Invention
[0006] The purpose of this invention is to provide an easy-tear high-barrier composite membrane and its preparation method. The method involves intercalating bentonite using iron-based pillar technology to effectively expand its interlayer spacing and specific surface area. Then, chitosan is double-bonded and grafted using a silane coupling agent to impart chemical polymerization activity to chitosan. Further composite modification of bentonite yields a chitosan / bentonite composite gel material. Finally, relying on a melt ring-opening reaction, a covalently bonded core-shell filler with stable interfacial bonding is constructed. This overcomes the technical bottlenecks of poor compatibility, easy aggregation, and weak interfacial bonding of traditional inorganic and organic fillers in polyamide matrices, thereby improving the overall quality of the composite membrane.
[0007] The objective of this invention can be achieved through the following technical solutions: A method for preparing an easy-tear high-barrier composite film includes the following steps: Step 1: Using ferric nitrate as the iron source and anhydrous sodium carbonate as the alkali source, stir at room temperature to promote the hydrolysis and polymerization of iron ions to form hydroxy iron oligomeric cations, thus obtaining the pillaring agent.
[0008] Step 2: Introduce the pillaring agent into the bentonite system. Relying on ion exchange, the agent is inserted between the bentonite layers to expand the layers and increase the interlayer spacing, thus obtaining pillared bentonite.
[0009] Step 3: Disperse chitosan in an ethanol / water mixture and perform siloxane condensation grafting with γ-methacryloxypropyltrimethoxysilane to introduce carbon-carbon double bonds into the chitosan macromolecule, thus obtaining double-bonded chitosan.
[0010] Step 4: Double-bonded chitosan is adsorbed onto the surface of the pillared bentonite sheets and enters the interlayer through hydrogen bonding and electrostatic interaction, resulting in a chitosan / bentonite composite gel material.
[0011] Step 5: The masterbatch A and masterbatch B are melt co-extruded, cast into sheets, and then simultaneously biaxially stretched, shaped, wound, and slit to obtain an easy-tear high-barrier composite film.
[0012] Furthermore, the specific preparation steps of the pillar proppant are as follows: Ferric nitrate and deionized water are added to a reaction vessel and stirred for 15-20 minutes at 20-25℃ and 500-550 r / min until dissolved. Then anhydrous sodium carbonate is added and stirring is continued for 2-4 hours. The mixture is then aged at room temperature for 24-26 hours to obtain the pillar proppant.
[0013] Furthermore, the ratio of ferric nitrate, deionized water, and anhydrous sodium carbonate is 6.06-6.28 g : 100-110 mL : 1.59-1.64 g.
[0014] Furthermore, the specific preparation steps of the pillared bentonite are as follows: Add bentonite and deionized water to a reaction vessel and stir for 15-20 min at 20-25℃ and 500-550 r / min. Then add pillaring agent, heat to 60-70℃ and continue stirring for 2-3 h. Aging at room temperature for 24-26 h, filter, wash the precipitate 2-4 times with deionized water and anhydrous ethanol, vacuum dry at 60-70℃ for 1-2 h, grind through a 100-mesh sieve to obtain pillared bentonite.
[0015] Furthermore, the ratio of bentonite, deionized water, and pillaring agent is 10-12g: 100-110mL: 30-40mL.
[0016] Furthermore, the specific preparation steps for double-bonded chitosan are as follows: Chitosan, anhydrous ethanol, and deionized water were added to a reaction vessel and stirred for 20-30 minutes at 50-60℃ and 500-600 r / min. Then, γ-methacryloyloxypropyltrimethoxysilane was added, and the pH was adjusted to 3-4 with hydrochloric acid solution. The reaction was continued for 6-8 hours. After filtration, the precipitate was washed 2-4 times with deionized water and anhydrous ethanol and dried under vacuum at 60-70℃ for 1-2 hours to obtain double-bonded chitosan.
[0017] Furthermore, the ratio of chitosan, anhydrous ethanol, deionized water, and γ-methacryloyloxypropyltrimethoxysilane is 25-30g: 1.5-1.7L: 3-4L: 110-112mL.
[0018] Furthermore, the specific preparation steps of the chitosan / bentonite composite gel material are as follows: Double-bonded chitosan and a 2-4% (w / w) acetic acid solution were added to a reaction vessel and stirred overnight at 50-60℃ and 500-600 rpm until fully dissolved. Then, pillared bentonite was added and stirring was continued for 2-3 hours. The resulting mixed solution was then poured into a 0.5-0.7 mol / L NaOH solution and stirred overnight. After thorough stirring, residual sodium hydroxide was removed by washing with deionized water. The mixture was then filtered and dried in an oven at 60-70℃ for 1-2 hours. Finally, it was ground and sieved to obtain the chitosan / bentonite composite gel material.
[0019] Furthermore, the ratio of double-bonded chitosan, acetic acid solution, and pillared bentonite is 5-7g: 500-550mL: 5-7g.
[0020] Furthermore, the specific preparation steps for covalently bonded core-shell fillers are as follows: Chitosan / bentonite composite gel material, POE maleic anhydride-grafted PA6, and di-tert-butyl peroxide are added to a high-speed mixer and mixed at 800-900 r / min for 10-12 min. The mixture is then transferred to a twin-screw extruder and melted and ring-opened at 185-190℃ and 250-300 r / min for 1-3 min. Granulation is then performed to obtain a covalently bonded core-shell filler.
[0021] Furthermore, the ratio of chitosan / bentonite composite gel material, POE maleic anhydride grafted PA6 and di-tert-butyl peroxide is 30-40g: 70-80g: 3-4g.
[0022] Furthermore, the A-layer masterbatch is obtained by melt blending and extrusion granulation of covalently bonded core-shell filler, PA6, poly(m-phenylene adipamide), silica, and oleamide in a mass ratio of 5-8:60-70:12-20:1-2:1-2 using a twin-screw extruder.
[0023] Furthermore, the B-layer masterbatch is obtained by melt blending and extrusion granulation of PA6, poly(m-phenylene adipamide), silica, and oleamide in a mass ratio of 60-70:12-20:1-2:1-2 using a twin-screw extruder.
[0024] The beneficial effects of this invention are: 1. This invention uses iron-based pillar technology to intercalate bentonite, effectively expanding its interlamellar spacing and specific surface area. Then, it uses a silane coupling agent to double-bond graft chitosan, endowing chitosan with chemical polymerization activity. Further, it uses composite modified bentonite to prepare chitosan / bentonite composite gel material. Finally, relying on melt ring-opening reaction, it constructs a covalently bonded core-shell filler with stable interfacial bonding, breaking through the technical bottleneck of poor compatibility, easy agglomeration, and weak interfacial bonding of traditional inorganic and organic fillers in polyamide matrix, and improving the overall quality of composite membrane. 2. This invention designs a biaxial stretching molding process using A / B dual-layer differentiated masterbatch co-extrusion. By using a functional layer of doped covalently bonded core-shell filler, controllable microphase separation is achieved, forming uniform stress concentration sites inside the film. This precisely solves the problem of the trade-off between barrier properties and tearability in traditional PA6 / MXD6 blend films, enabling the composite film to have both excellent straight-line tear performance and high and low air and water vapor permeability. Combined with a silica and oleamide compound additive system, the film processing performance and molding quality are effectively optimized. Detailed Implementation
[0025] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0026] Example 1: A method for preparing an easy-tear high-barrier composite film, comprising the following steps: S1: Add 6.06g of ferric nitrate and 100mL of deionized water to the reaction vessel, stir for 15min at 20℃ and 500r / min until dissolved, then add 1.59g of anhydrous sodium carbonate, continue stirring for 2h, and age at room temperature for 24h to obtain the pillar proppant.
[0027] S2: Add 10g of bentonite and 100mL of deionized water to the reactor, stir for 15min at 20℃ and 500r / min, then add 30mL of pillaring agent, heat to 60℃ and continue stirring for 2h, age at room temperature for 24h, filter, wash the precipitate twice with deionized water and anhydrous ethanol, vacuum dry at 60℃ for 1h, grind through a 100-mesh sieve to obtain pillared bentonite.
[0028] S3: Add 25g chitosan, 1.5L anhydrous ethanol and 3L deionized water to a reaction vessel and stir for 20min at 50℃ and 500r / min. Then add 110mL γ-methacryloyloxypropyltrimethoxysilane, adjust the pH to 3 with hydrochloric acid solution, and continue stirring for 6h. Filter, wash the precipitate twice with deionized water and anhydrous ethanol, and dry under vacuum at 60℃ for 1h to obtain double-bonded chitosan.
[0029] S4: Add 5g of double-bonded chitosan and 500mL of 2% acetic acid solution to the reactor. Stir overnight at 50℃ and 500r / min until fully dissolved. Then add 5g of pillared bentonite and continue stirring for 2h. Pour the resulting mixed solution into 0.5mol / L NaOH solution and continue stirring overnight. After thorough stirring, wash with deionized water to remove residual sodium hydroxide. Then filter and separate, dry in an oven at 60℃ for 1h, grind and sieve to obtain chitosan / bentonite composite gel material.
[0030] S5: 30g of chitosan / bentonite composite gel material, 70g of POE maleic anhydride-grafted PA6, and 3g of di-tert-butyl peroxide were added to a high-speed mixer and mixed at 800r / min for 10min. The mixture was then transferred to a twin-screw extruder and melted and ring-opened at 185℃ and 250r / min for 1min. The mixture was then granulated to obtain a covalently bonded core-shell filler.
[0031] S6: 5g of covalently bonded core-shell filler, 60g of PA6, 12g of poly(m-phenylene adipamide), 1g of silica, and 1g of oleamide are melt-blended and extruded into granules using a twin-screw extruder to obtain layer A masterbatch; 60g of PA6, 12g of poly(m-phenylene adipamide), 1g of silica, and 1g of oleamide are melt-blended and extruded into granules using a twin-screw extruder to obtain layer B masterbatch; layer A masterbatch and layer B masterbatch are melt-co-extruded, cast into sheets, and then simultaneously biaxially stretched, shaped, wound, and slit to obtain an easy-tear high-barrier composite film.
[0032] Example 2: A method for preparing an easy-tear high-barrier composite film, comprising the following steps: S1: Add 6.17g of ferric nitrate and 105mL of deionized water to the reaction vessel, stir for 17.5min at 22.5℃ and 525r / min until dissolved, then add 1.615g of anhydrous sodium carbonate, continue stirring for 3h, and age at room temperature for 25h to obtain the pillar proppant.
[0033] S2: Add 11g of bentonite and 105mL of deionized water to the reactor and stir for 17.5min at 22.5℃ and 525r / min. Then add 35mL of pillaring agent, heat to 65℃ and continue stirring for 2.5h. Aging at room temperature for 25h, filter, wash the precipitate three times with deionized water and anhydrous ethanol, vacuum dry at 65℃ for 1.5h, grind through a 100-mesh sieve to obtain pillared bentonite.
[0034] S3: Add 27.5g chitosan, 1.6L anhydrous ethanol and 3.5L deionized water to a reaction vessel and stir for 25min at 55℃ and 550r / min. Then add 111mL γ-methacryloyloxypropyltrimethoxysilane, adjust the pH to 3.5 with hydrochloric acid solution, and continue stirring for 7h. Filter, wash the precipitate three times with deionized water and anhydrous ethanol, and dry under vacuum at 65℃ for 1.5h to obtain double-bonded chitosan.
[0035] S4: Add 6g of double-bonded chitosan and 525mL of 3% acetic acid solution to the reactor. Stir overnight at 55℃ and 550r / min until fully dissolved. Then add 6g of pillared bentonite and continue stirring for 2.5h. Pour the resulting mixed solution into 0.6mol / L NaOH solution and continue stirring overnight. After thorough stirring, wash with deionized water to remove residual sodium hydroxide. After filtration and separation, dry in an oven at 65℃ for 1.5h, grind and sieve to obtain chitosan / bentonite composite gel material.
[0036] S5: 35g of chitosan / bentonite composite gel material, 75g of POE maleic anhydride-grafted PA6, and 3.5g of di-tert-butyl peroxide were added to a high-speed mixer and mixed at 850r / min for 11min. The mixture was then transferred to a twin-screw extruder and melted and ring-opened at 187.5℃ and 275r / min for 2min. The mixture was then granulated to obtain a covalently bonded core-shell filler.
[0037] S6: 6g of covalently bonded core-shell filler, 65g of PA6, 16g of poly(m-phenylene adipamide), 1.5g of silica, and 1.5g of oleamide are melt-blended and extruded into granules using a twin-screw extruder to obtain layer A masterbatch; 65g of PA6, 16g of poly(m-phenylene adipamide), 1.5g of silica, and 1.5g of oleamide are melt-blended and extruded into granules using a twin-screw extruder to obtain layer B masterbatch; layer A masterbatch and layer B masterbatch are melt-co-extruded, cast into sheets, and then simultaneously biaxially stretched, shaped, wound, and slit to obtain an easy-tear high-barrier composite film.
[0038] Example 3: A method for preparing an easy-tear high-barrier composite film, comprising the following steps: S1: Add 6.28g of ferric nitrate and 110mL of deionized water to the reaction vessel, stir for 20min at 25℃ and 550r / min until dissolved, then add 1.64g of anhydrous sodium carbonate, continue stirring for 4h, and age at room temperature for 26h to obtain the pillar proppant.
[0039] S2: Add 12g of bentonite and 110mL of deionized water to the reactor and stir for 20min at 25℃ and 550r / min. Then add 40mL of pillaring agent, heat to 70℃ and continue stirring for 3h. Aging at room temperature for 26h, filter, wash the precipitate 4 times with deionized water and anhydrous ethanol, vacuum dry at 70℃ for 2h, grind through a 100-mesh sieve to obtain pillared bentonite.
[0040] S3: Add 30g chitosan, 1.7L anhydrous ethanol and 4L deionized water to a reaction vessel and stir for 30min at 60℃ and 600r / min. Then add 112mL γ-methacryloyloxypropyltrimethoxysilane, adjust the pH to 4 with hydrochloric acid solution, and continue stirring for 8h. Filter, wash the precipitate 4 times with deionized water and anhydrous ethanol, and dry under vacuum at 70℃ for 2h to obtain double-bonded chitosan.
[0041] S4: Add 7g of double-bonded chitosan and 550mL of 4% acetic acid solution to the reactor. Stir overnight at 60℃ and 600r / min until fully dissolved. Then add 7g of pillared bentonite and continue stirring for 3h. Pour the resulting mixed solution into 0.7mol / L NaOH solution and continue stirring overnight. After thorough stirring, wash with deionized water to remove residual sodium hydroxide. After filtration and separation, dry in an oven at 70℃ for 2h, grind and sieve to obtain chitosan / bentonite composite gel material.
[0042] S5: 40g of chitosan / bentonite composite gel material, 80g of POE maleic anhydride-grafted PA6, and 4g of di-tert-butyl peroxide were added to a high-speed mixer and mixed at 900r / min for 12min. The mixture was then transferred to a twin-screw extruder and melted and ring-opened at 190℃ and 300r / min for 3min. The mixture was then granulated to obtain a covalently bonded core-shell filler.
[0043] S6: 8g of covalently bonded core-shell filler, 70g of PA6, 20g of poly(m-phenylene adipamide), 2g of silica, and 2g of oleamide are melt-blended and extruded and granulated using a twin-screw extruder to obtain layer A masterbatch; 70g of PA6, 20g of poly(m-phenylene adipamide), 2g of silica, and 2g of oleamide are melt-blended and extruded and granulated using a twin-screw extruder to obtain layer B masterbatch; layer A masterbatch and layer B masterbatch are melt-co-extruded, cast into sheets, and then simultaneously biaxially stretched, shaped, wound, and slit to obtain an easy-tear high-barrier composite film.
[0044] Comparative Example 1: Based on Example 3, the pillar-supporting bentonite in step S4 was replaced with the raw material bentonite in step S2.
[0045] Comparative Example 2: Based on Example 3, the double-bonded chitosan in step S4 was replaced with the raw chitosan in step S2.
[0046] Comparative Example 3: Based on Example 3, the covalently bonded core-shell filler in step S6 was replaced with POE maleic anhydride-grafted PA6 in step S5.
[0047] Performance tests were conducted on Examples 1-3 and Comparative Examples 1-3, and the results are shown in Table 1: Table 1 Peel strength (N / 15mm) 5.2 5.7 6.1 4.5 4.1 3.6 GB / T 8808-1988 <![CDATA[Oxygen transmission rate (cc / m 2 ·day)]]> 1.9 1.6 1.3 2.6 3.3 4.2 GB / T 1038 <![CDATA[Water vapor transmission rate (g / m 2 ·day)]]> 2.5 2.2 2.0 3.8 4.7 5.6 GB / T 1037 Haze (%) 2.9 2.7 2.8 4.6 5.8 7.2 GB / T 2410-2008 Tear force (N) 3.8 4.1 4.4 2.9 2.4 2.0 GB / T 16578.1-2018 As shown in Table 1, in Comparative Example 1, the original bentonite sheets were tightly stacked with small interlayer spacing and few active sites. Chitosan could only be adsorbed on the powder surface and had difficulty penetrating into the interior of the sheets. The powder had a low specific surface area, resulting in a significant decrease in the barrier synergistic effect of the core-shell filler prepared subsequently. Simultaneously, the filler dispersion uniformity in the polyamide matrix deteriorated, leading to uneven distribution of stress concentration points within the film. The final results showed a significant deterioration in oxygen and water vapor barrier performance, an increase in haze, and a slight decrease in peel strength.
[0048] In Comparative Example 2, chitosan lacks polymerizable carbon-carbon double bonds, making it unable to undergo free radical covalent grafting with POE-g-PA6 during melt processing. The two-phase physical bonding relies solely on hydrogen bonds and van der Waals forces, resulting in weak interfacial bonding in the core-shell structure. The filler is prone to detachment from the matrix under external forces, generating numerous interfacial defects. These defects not only create gas diffusion channels but also disrupt stress transmission, leading to poor tear straightness, increased film haze, and reduced interlayer peel strength.
[0049] Comparative Example 3 lacks covalently bonded core-shell fillers, lacks two-dimensional sheet barrier structures, and lacks uniformly distributed rigid stress concentration sites. On the one hand, it loses the bentonite sheet tortuous path effect, resulting in a significant reduction in barrier performance; on the other hand, it cannot form a stable and uniform microphase separation structure, leading to a poorer tear-resistant effect; and simple elastomer toughening easily causes a decrease in film rigidity, an increase in interface defects, a simultaneous decline in peel strength and barrier properties, and a significant increase in haze.
[0050] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and variations can be made to these embodiments without departing from the principles and spirit of the invention.
Claims
1. A method for preparing an easy-tear high-barrier composite film, characterized in that, Includes the following steps: Step 1: Using ferric nitrate as the iron source and anhydrous sodium carbonate as the alkali source, stir at room temperature to promote the hydrolysis and polymerization of iron ions to form hydroxy iron oligomeric cations, thus obtaining the pillaring agent; Step 2: Introduce the pillaring agent into the bentonite system. Relying on ion exchange, the agent is inserted between the bentonite layers to expand the layers and increase the interlayer spacing, thus obtaining pillared bentonite. Step 3: Disperse chitosan in an ethanol / water mixture and perform siloxane condensation grafting with γ-methacryloyloxypropyltrimethoxysilane to introduce carbon-carbon double bonds into the chitosan macromolecule, thus obtaining double-bonded chitosan. Step 4: Double-bonded chitosan is adsorbed onto the surface of pillared bentonite sheets and enters the interlayer through hydrogen bonding and electrostatic interaction to obtain chitosan / bentonite composite gel material; Step 5: The masterbatch of layer A and layer B is melt-co-extruded, cast into sheets, and then simultaneously biaxially stretched, shaped, wound, and slit to obtain an easy-tear high-barrier composite film.
2. The method for preparing an easy-tear high-barrier composite film according to claim 1, characterized in that, The specific preparation steps for the pillaring agent are as follows: Add ferric nitrate and deionized water to a reaction vessel and stir for 15-20 minutes at 20-25℃ and 500-550r / min until dissolved. Then add anhydrous sodium carbonate and continue stirring for 2-4 hours. Aging at room temperature for 24-26 hours yields the pillar proppant. The ratio of ferric nitrate, deionized water, and anhydrous sodium carbonate used is 6.06-6.28g: 100-110mL: 1.59-1.64g.
3. The method for preparing an easy-tear high-barrier composite film according to claim 1, characterized in that, The specific preparation steps of the pillared bentonite are as follows: Add bentonite and deionized water to a reaction vessel and stir for 15-20 min at 20-25℃ and 500-550 r / min. Then add pillaring agent, heat to 60-70℃ and continue stirring for 2-3 h, age at room temperature for 24-26 h, filter, wash the precipitate 2-4 times with deionized water and anhydrous ethanol, vacuum dry at 60-70℃ for 1-2 h, grind through a 100-mesh sieve to obtain pillared bentonite. The ratio of bentonite, deionized water and pillaring agent is 10-12g: 100-110mL: 30-40mL.
4. The method for preparing an easy-tear high-barrier composite film according to claim 1, characterized in that, The specific preparation steps for the double-bonded chitosan are as follows: Chitosan, anhydrous ethanol, and deionized water were added to a reaction vessel and stirred for 20-30 minutes at 50-60℃ and 500-600 r / min. Then, γ-methacryloyloxypropyltrimethoxysilane was added, and the pH was adjusted to 3-4 with hydrochloric acid solution. The reaction was continued for 6-8 hours. The mixture was filtered, and the precipitate was washed 2-4 times with deionized water and anhydrous ethanol. The precipitate was then dried under vacuum at 60-70℃ for 1-2 hours to obtain double-bonded chitosan. The ratio of chitosan, anhydrous ethanol, deionized water and γ-methacryloyloxypropyltrimethoxysilane is 25-30g: 1.5-1.7L: 3-4L: 110-112mL.
5. The method for preparing an easy-tear high-barrier composite film according to claim 1, characterized in that, The specific preparation steps of the chitosan / bentonite composite gel material are as follows: Double-bonded chitosan and a 2-4% (w / w) acetic acid solution were added to a reaction vessel and stirred overnight at 50-60℃ and 500-600 rpm until fully dissolved. Then, pillared bentonite was added and stirring was continued for 2-3 hours. The resulting mixed solution was then poured into a 0.5-0.7 mol / L NaOH solution and stirred overnight. After thorough stirring, residual sodium hydroxide was removed by washing with deionized water. The mixture was then filtered and dried in an oven at 60-70℃ for 1-2 hours. Finally, it was ground and sieved to obtain the chitosan / bentonite composite gel material.
6. The method for preparing an easy-tear high-barrier composite film according to claim 5, characterized in that, The ratio of double-bonded chitosan, acetic acid solution, and pillared bentonite is 5-7g: 500-550mL: 5-7g.
7. The method for preparing an easy-tear high-barrier composite film according to claim 1, characterized in that, The specific preparation steps for the covalently bonded core-shell filler are as follows: Chitosan / bentonite composite gel material, POE maleic anhydride-grafted PA6, and di-tert-butyl peroxide are put into a high-speed mixer and mixed at 800-900 r / min for 10-12 min. The mixture is then transferred to a twin-screw extruder and melted and ring-opened at 185-190℃ and 250-300 r / min for 1-3 min. The mixture is then granulated to obtain a covalently bonded core-shell filler. The ratio of chitosan / bentonite composite gel material, POE maleic anhydride grafted PA6 and di-tert-butyl peroxide is 30-40g: 70-80g: 3-4g.
8. The method for preparing an easy-tear high-barrier composite film according to claim 1, characterized in that, The A-layer masterbatch is obtained by melt blending and extrusion granulation of covalently bonded core-shell filler, PA6, poly(m-phenylene adipamide), silica, and oleamide in a mass ratio of 5-8:60-70:12-20:1-2:1-2 using a twin-screw extruder.
9. The method for preparing an easy-tear high-barrier composite film according to claim 8, characterized in that, The B-layer masterbatch is obtained by melt blending and extrusion granulation of PA6, poly(m-phenylene adipamide), silica, and oleamide in a mass ratio of 60-70:12-20:1-2:1-2 using a twin-screw extruder.
10. An easy-tear high-barrier composite film, characterized in that, It is prepared by the preparation method described in any one of claims 1-9.
Citation Information
Patent Citations
An antibacterial high-barrier easy-tear composite film and its preparation method
CN109774281B